Hydroxylated phenylacetamides derived from bioactive benzoxazinoids are bioavailable in humans after habitual consumption of whole grain sourdough rye bread. Issue 10 (16th May 2013) - Beckmann, Manfred; Lloyd, Amanda J.; Haldar, Sumanto; Seal, Chris; Brandt, Kirsten; Draper, John
<x xml:space="preserve">Abstract</x> Scope Understanding relationships between dietary whole grain and health is hindered by incomplete knowledge of potentially bioactive metabolites derived from these foods. We aimed to discover compounds in urine correlated with changes in amounts of whole grain rye consumption. Methods and results After a wash‐out period, volunteers consumed 48‐g whole grain rye foods per day for 4 wk and then doubled their intake for a further 4 wk. Samples of 24‐h urines were analyzed by flow infusion electrospray MS followed by supervised multivariate data analysis. Urine samples from participants who reported high intakes of rye flakes, rye pasta, or total whole grain rye products could not be discriminated adequately from their wash‐out samples. However, discrimination was seen in urine samples from participants who reported high whole grain sourdough rye bread consumption. Accurate mass analysis of explanatory signals followed by fragmentation identified conjugates of the benzoxazinoid lactam 2‐hydroxy‐1, 4‐benzoxazin‐3‐one and hydroxylated phenyl acetamide derivatives. Statistical validation showed sensitivities of 84–96% and specificities of 70–81% (p values < 0·05) for elevated concentrations of these signals after preferential whole grain sourdough rye bread consumption. Conclusion Several potentially bioactive alkaloids have been identified in humans consuming fermented whole grain sourdough rye bread.